(untitled) (The Journal of Building and Land Development, 2020)
This study investigated flood risks facing businesses operating in flood-prone areas. In these areas, businesses are conducted despite frequent floods. A case study strategy was adopted by deploying in-depth interviews of ten purposively selected businesses. The business ventures were picked from public and private entities. Qualitative data were collected using open-ended questionnaires and observations and were analyzed using MAXQDA software. Major findings include: destruction of buildings, office equipment and tradable goods. Additionally, accumulation of solid waste in business premises, disruption of transport and other amenities like electricity and water was also observed. Although business people hesitated to disclose their incomes during dry season, there was a decrease in foreseen income due to a decrease of customers and business closure. Moreover, income loss was compounded by an upsurge in maintenance costs and in shifting goods to more secure areas during floods. The study concludes that flood risks seldom deter entrepreneurs from continuing with business. Nevertheless, there is a need to: regulate and control business operations in hazardous areas; enforce development control measures and engaging business operators in finding solutions and implement flood mitigation initiatives. Â Key words: Flood prone areas, Flood risks, Business operations